Causal relationship between obesity and iron deficiency anemia: a two-sample Mendelian randomization study - Wang, Tingting; Gao, Qi; Yao, Yuanyuan; Luo, Ge; Lv, Tao; Xu, Guangxin; Liu, Mingxia; Xu, Jingpin; Li, Xuejie; Sun, Dawei; Cheng, Zhenzhen; Wang, Ying; et al. (Frontiers in Public Health, 2023)
Background Observational studies have suggested an association between obesity and iron deficiency anemia, but such studies are susceptible to reverse causation and residual confounding. Here we used Mendelian randomization to assess whether the association might be causal. Methods Data on single-nucleotide polymorphisms that might be associated with various anthropometric indicators of obesity were extracted as instrumental variables from genome-wide association studies in the UK Biobank. Data on genetic variants in iron deficiency anemia were extracted from a genome-wide association study dataset within the Biobank. Heterogeneity in the data was assessed using inverse variance-weighted regression, Mendelian randomization Egger regression, and Cochran's Q statistic. Potential causality was assessed using inverse variance-weighted, Mendelian randomization Egger, weighted median, maximum likelihood and penalized weighted median methods. Outlier SNPs were identified using Mendelian randomization PRESSO analysis and “leave-one-out” analysis. Results Inverse variance-weighted regression associated iron deficiency anemia with body mass index, waist circumference, trunk fat mass, body fat mass, trunk fat percentage, and body fat percentage (all odds ratios 1.003–1.004, P ≤ 0.001). Heterogeneity was minimal and no evidence of horizontal pleiotropy was found. Conclusion Our Mendelian randomization analysis suggests that obesity can cause iron deficiency anemia.